STRATEGI KEPALA SEKOLAH DALAM PEMBENTUKAN SIKAP TOLERANSI UMAT BERAGAMA KEPADA PESERTA DIDIK - Ningsih, Eka Fitria; Setiawan, Fitra; Ningsih, Sri Rahayu (STAI Darul Qalam Tangerang, 2023)
Learning strategies are very useful for educators as well as students in the learning process. For educators, this learning strategy serves as a basis as well as a reference for activities that should be organized according to the system for carrying out learning. Each attitude learning strategy usually directs students to situations that should involve conflict or problematic situations. In this situation, students are expected to be able to draw decisions on the basis of values ​​that they think should be good. In emphasizing learning strategies that should be able to shape personality. Its function is for students to care about others. Cognitive development is a cognitive reorganization procedure that should occur gradually in a certain sequence. Forming tolerance in the learning environment is a wise and fair attitude of school principals and educators. That is why the righteous are always impartial, the attitude that should only be on the side of the truth. Forming an attitude of tolerance between religious communities in the learning environment is to form an attitude of mutual respect and respect for others. Respect for other people is one of the efforts to develop unity and also harmony between humans, so that social life that should respect and respect each other can be realized in accordance with human dignity and worth